(untitled) (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2013)
Today scientists are in research to create an artificial brain that can think, respond, take decision, and keep anything in memory. The main aim is to upload human brain into machine. So that man can think, take decision without any effort. After the death of the body, the virtual brain will act as the man. So, even after the death of a person we will not loose the knowledge, intelligence, personalities, feelings and memories of that man, that can be used for the development of the human society. Technology is growing faster than every thing. IBM is now in research to create a virtual brain, called Blue brain. If possible, this would be the first virtual brain of the world. IBM, in partnership with scientists at Switzerlands Ecole Polytech- nique Federale de Lausannes (EPFL) Brain and Mind Institute will begin simulating the brains biological systems and output the data as a working 3-dimensional model that will recreate the high-speed electrochemical interactions that take place within the brains interior. These include cognitive functions such as language, learning, perception and memory in addition to brain malfunction such as psychiatric disorders like depression and autism. From there, the modeling will expand to other regions of the brain and, if successful, shed light on the relationships between genetic, molecular and cognitive functions of the brain.